ANALISIS USAHA TERNAK AYAM PEDAGING MITRA DAN NON MITRA PT ABC DI KABUPATEN LAMPUNG TIMUR - Adelia, Yosefine; Haryono, Dwi; Nugraha, Adia (Jurnal Ilmu-Ilmu Agribisnis, 2025)
The objectives of this study are to (1) clarify the current cooperative model of the cooperative and PT ABC,  (2) analyze the cost structure of poultry farming between the cooperative and other PT ABC members, and. (3) analyze performance of poultry farming by comparing poultry farming affiliated to.  PT ABC and those unaffiliated  This study was conducted in East Lampung District .  This study was conducted from  October to December 2023.  The respondents were 35 PT-ABC breeders and 10 non-PT-ABC breeders.  The data analysis were utilised  a descriptive income analysis, and an independent t-test.  The research results show that (1) the current cooperation system between breeders and PT ABC is an important plasma cooperation and (2) the cost structure ratios of partner companies of PT ABC and other companies have the same standards.  There are significant differences in costs, seed cost (DOC), labor and (3) yield per kg between PT ABC member farmers and non-member farmers. Key words: income, livestock business, partnership